2020
DOI: 10.1016/j.cam.2019.112397
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of an adaptive discontinuous Galerkin method for elliptic interface problems

Abstract: We prove a basic error contraction result of an adaptive discontinuous Galerkin method for an elliptic interface problem. The interface conditions considered model mass transfer of solutes through semipermeable membranes and other filtering processes. The adaptive algorithm is based on a residualtype a posteriori error estimator, with a bulk refinement criterion. The a posteriori error bound is derived under the assumption that the triangulation is aligned with the interfaces although, crucially, extremely gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The stiff part is treated by an implicit scheme, while an explicit scheme treats the second part. The main important point in our preferred method is to reduce the number of iterations and, as a result, cause a decrease in the scheme's computational time; for more detail about numerical methods, see [22][23][24][25][26][27][28]. It can be seen that the approximate solutions of the whole and minimized models are incredibly close.…”
Section: Discussionmentioning
confidence: 99%
“…The stiff part is treated by an implicit scheme, while an explicit scheme treats the second part. The main important point in our preferred method is to reduce the number of iterations and, as a result, cause a decrease in the scheme's computational time; for more detail about numerical methods, see [22][23][24][25][26][27][28]. It can be seen that the approximate solutions of the whole and minimized models are incredibly close.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this will give insight about designing adaptive algorithm, which allow use to control the cost of computations. In the future, this Chapter can be extended to the fully discrete case for semilinear parabolic interface problems in L ∞ L 2 ðÞ þ L 2 H 1 ÀÁ and L ∞ L 2 ðÞ norms [18,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Whenever first-order IMEX-RK techniques have generally been applied to deals with the stiff terms of the chemistry implicitly in combustion simulations and hypersonic flow, two IMEX-RK techniques are fourth-order accurate. As a result, there have been several studies that have attracted much interest, and many numerical schemes, like the Euler method, Runge Kutta method, multistep schemes [17-20], Finite difference method [21, [34][35][36][37][38][39][40], and Finite element methods [22][23][24][25], have been proposed over time.…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…The findings of that work indicated that healthcare operations must focus more on the original model parameters. This model can be estimated by using finite element methods see [35][36][37][38][39].…”
Section: Numerical Experimentsmentioning
confidence: 99%